Effectiveness of Background Music on Aggressive Behavior of Intellectually Disabled Children - Nida Gul, Hafiz Tahir Jameel, Muhammad Naeem Mohsin (JIE, 2024)
Children with intellectual disabilities show some behavioral and emotional problems especially in school setting like physical and verbal aggression. The purpose of this research is to find out the effectiveness of background music to reduce the aggressive behavior in intellectually disabled children in the classroom. Sample included 40 aggressive students aged between 6 to 16 years, studying in a special education center. Aggression questionnaire of Arnold Buss and Mark Perry was used to gather the responses. Two groups were made by random sampling technique. Experimental group received background music from western classical and new age music pieces with binaural beats for 24 consecutive weeks. Structured music program was played for 120 minutes after the school brake. Control group did not receive any kind of treatment. After treatment the experimental group exhibit significant decrease in aggression. The t-test was used for the comparison of statistical data analysis for both groups. Background music was noted to be effective in the classroom to reduce aggression in children.